Light-Induced Ostwald Ripening of Organic Nanodots to Rods - Mahesh, Sankarapillai; Gopal, Anesh; Thirumalai, Rajasekaran; Ajayaghosh, Ayyappanpillai (Journal of the American Chemical Society, 2012)
Ostwald ripening allows the synthesis of 1D nanorods of metal and semiconductor nanoparticles. However, this phenomenon is unsuccessful with organic π-systems due to their spontaneous self-assembly to elongated fibers or tapes. Here we demonstrate the uses of light as a versatile tool to control the ripening of amorphous organic nanodots (ca. 15 nm) of an azobenzene-derived molecular assembly to micrometer-sized supramolecular rods. A surface-confined dipole variation associated with a low-yield (13–14%) trans–cis isomerization of the azobenzene moiety and the consequent dipole–dipole interaction in a nonpolar solvent is believed to be the driving force for the ripening of the nanodots to rods.